Targeting FOXP1 phase separation in small cell lung cancer mechanisms of chemotherapy resistance - Tang, Yichun; Niu, Yuchun; Chen, Yi; Zhou, Xuyang; Hu, Yueyang; Sun, Lei; Xiong, Yan; Xu, Yue; Wang, Qiongyao; Wang, Yu; Guo, Linlang (Communications biology, 2025)
Our study elucidates the role of FOXP1 in chemoresistance in small cell lung cancer(SCLC). FOXP1 enhances chemoresistance by regulating SP8 expression through its super-enhancer (SP8-SE), with SP8 mediating resistance via the homologous recombination repair (HRR) pathway. We also discovered that FOXP1 forms punctate nuclear structures indicative of liquid-liquid phase separation, crucial for its transcriptional regulation. Targeting the FOXP1-SP8-HR axis with BRD4 and PARP inhibitors showed synergistic effects in reducing tumor growth in vitro and in patient-derived xenograft models. These findings identify FOXP1 as a critical mediator and marker of chemoresistance in SCLC, providing a foundation for developing targeted therapies to overcome this resistance.
Gesehen am 14.08.2025